Protecting Research Subjects — What Must Be Done - Shalala, Donna (The New England journal of medicine, 2000)
As we race toward the as yet unimagined scientific and medical triumphs of the 21st century, no one is more hopeful about the journey than I am. Nevertheless, moving ahead with cutting-edge research must not mean leaving behind well-established international standards for protecting human subjects in clinical trials. None of these principles is more important than the protection of research subjects by informed consent based on full disclosure of potential risks and benefits. I did not expect, or want, to complete my tenure as secretary of health and human services by raising questions about the safety of patients in clinical . . .